Implementation of Planning Services in Planning The Needs of State Civil Servants in Klungkung Regency - Ni Made Juniantari; Ni Wayan Widhiasthini (Dinasti Publisher, 2025)
Planning the needs of the State Civil Apparatus (ASN) is an important part of bureaucratic reform to increase the effectiveness and efficiency in the management of human resources of the apparatus. The Klungkung Regency Government has adopted the State Civil Apparatus Information System (SIASN) Planning Service to improve the quality of planning for the needs of the State Civil Apparatus. Previously, planning the needs of State Civil Apparatus employees in Klungkung Regency was carried out manually or not through a nationally integrated system. This study aims to analyze the implementation of SIASN Planning Services in Klungkung Regency and identify its inhibiting factors. Using a qualitative approach, data is obtained through interviews, observations, and documentation. The results of the study show that the implementation of SIASN Planning Services in Klungkung Regency has provided benefits in data integration and planning transparency. However, there are still obstacles such as limited skilled human resources, data mismatches in the system, and lack of socialization and training for users. This study recommends increasing user capacity, improving systems, and improving infrastructure support to optimize the implementation of SIASN Planning Services.